Rurban Centres: The New Dimension of Urbanism. (2016) - Kolhe, Neha Pranav; Dhote, Krishna Kumar
Abstract: In recent years urbanization has become synonym to development. Developing countries like India has experienced huge shift in the economy from agrarian base to service oriented employment. Indian cities unlike the western are not planned; they evolve in layers as a testimony to different period. The settlement may be organic, with heterogeneity yet very well reflects the interwoven social fabric. As a result of urbanization the urban sprawl is approaching the rural hinterlands. The line of distinction is fading away between urban and rural. A new type of settlement is emerging which once termed as conurbation by the Scottish planner Patrick Geddes. The area with diffusion of urban and rural activities is termed as RURBAN. These rurbancentres are new emerging towns that are governed by rural local bodies, the activities possess in these areas are urban in nature. The paper attempts to develop a understanding of issues and challenges, possibilities and potential and development guidelines for this upcoming new centres of urban growth.